Representasi Kesetaraan Gender dalam Konten TikTok sebagai Media Layanan Bimbingan dan Konseling - Malikatul Muluk; Nur Hafizatun Nisa; Firda Destiawati; Hendrik Sulistiawati; Anis Muyassaroh Khoirun Nisa; Chandra Duwita Ela Pradana (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
Social media, particularly TikTok, has become an influential space for adolescents in shaping social understanding and attitudes, including perspectives on gender equality. This study aims to analyze the representation of gender equality in TikTokcontent and examine its potential as a medium for Guidance and Counseling services. The research employs a descriptive qualitative approach using qualitative content analysis. Data were collected through non-participant observation and documentation of TikTokvideos containing messages related to gender equality, including narratives, visual elements, and symbolic representations. The findings indicate that TikTokcontent represents gender equality through the depiction of equal gender roles, the rejection of discriminatory gender stereotypes, and an emphasis on respect and justice in social relationships. These messages are conveyed through contextual communication styles and engaging audiovisual formats that are easily understood by adolescents. The study also reveals that TikTokhas potential as a supportive medium for Guidance and Counseling services, particularly in informational, preventive, and developmental services.